2012
DOI: 10.4269/ajtmh.2012.11-0350
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Two Malaria Rapid Diagnostic Tests in Febrile Adult Patients with and without Human Immunodeficiency Virus-1 Infection in Blantyre, Malawi

Abstract: The performance of two histidine-rich protein type-2–based malaria rapid diagnostic tests (mRDTs) was examined in a rural area with a high prevalence of malaria and human immunodeficiency virus type-1 (HIV-1) infection in 113 and 445 febrile patients ≥ 15 years of age with and without HIV-1 infection, respectively. Patients were tested for HIV-1 infection by using a standard assay and for Plasmodium falciparum by using two mRDTs and microscopy. When microscopy was used as the gold standard, both mRDTs performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…19 Generally, at lower parasitaemia, variability in sensitivity is more common. 20,38,39 Similar observation of false negative MRDT results at parasite counts even higher than 1000 cells/µL have been reported in other studies 19,25,40,41 and may be attributed to prozone effect observed with immunochromatographic tests such as MRDT. 42 All the same, many MRDTs today can achieve excellent sensitivity and specificity for P. falciparum at parasite density lower than 500 cells/µL.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…19 Generally, at lower parasitaemia, variability in sensitivity is more common. 20,38,39 Similar observation of false negative MRDT results at parasite counts even higher than 1000 cells/µL have been reported in other studies 19,25,40,41 and may be attributed to prozone effect observed with immunochromatographic tests such as MRDT. 42 All the same, many MRDTs today can achieve excellent sensitivity and specificity for P. falciparum at parasite density lower than 500 cells/µL.…”
Section: Discussionsupporting
confidence: 84%
“…19 Contrary to our results, a 100% sensitivity and similar specificity of about 95.4% was documented in a Burkina Faso study among HIV-positive participants. 21 Other studies on MRDT performance among HIV-positive population in Malawi, 25 and two different studies in Uganda 10,20 have shown higher sensitivity of over 94%. In these studies, the specificities averaged over 97% like in ours except for the Malawi study that reported about 51% specificity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…RDTs have been shown to be a cost-effective measure to ensure malaria treatment is directed to those who are infected [22,23]. In Mutasa District, the use of RDT increased to approximately 80% of suspected cases and up to 75% of RDT were positive.…”
Section: Discussionmentioning
confidence: 99%